Nolator-norator models of electronic elements and active circuits - Єгоршин, Ю. О.; Красноусова, О. Ю. (Proceedings of National Aviation University (archive), 2021)
In this article we suggest complete nolator-norator models of active line quadruples and adjusted models of real transistors and operational amplifiers of different types. We also prove different approximate models of transistors. We offer nolator model of current distributor intensifier at first. The model of operational amplifiers also takes into account the presence of basic blocks and nonlinear blocks of the transmissive characteristic.